Real Estate in China: Consumer Behaviour of the Middle Class - Lee, Yan Yan (2013)
This research examines middle class consumer behaviour in the real estate market in China. The study aims to explore the factors that motivate behaviour middle class people in China to purchase real estate. The research focuses on the perceptions of Chinese middle class consumers of housing and behaviour the reasons that they invest in property.